(untitled) (Dhaka University Journal of Science, 2022)
For normal physiologic functions, Iodine is necessary in small amount. It sanctions the thyroid gland to creates thyroid hormones, which is essential for mature and enlargement of the brain, body structures and central nervous system (CNS). In developing countries mental impediment and insufficient commercial performance are one of the results of iodine insufficiency issue. Globally, universal salt iodization has been executed to eradicate iodine insufficiency. However, the sufficiency of iodine in salts needs close observing to match its deliberated target. From this study,we find the adequately iodized salt consumption is associated with some demographic features such as, education, region, wealth index, access to mass-media etc. These findings are important for policy makers and Government as they should take necessary steps to increase the accession to education and media and also take realistic plan to increase the availability of adequately salt in Bangladesh. Dhaka Univ. J. Sci. 70(2): 1-7, 2022 (July)